Acupuncture for Impaired Glucose Tolerance in People With Obesity: A Protocol for a Multicenter Randomized Controlled Trial - Yan, Yan; Sun, Yuanjie; Wang, Xinlu; Zhu, Lili; Chen, Yu; Liu, Zhishun (Frontiers in Medicine, 2022)
Background Impaired glucose tolerance (IGT) is associated with being overweight/obesity and is a powerful risk factor for the disease of diabetes. In addition to lifestyle intervention that shows limited clinical application, acupuncture treatment has been a feasible treatment method for IGT in clinical practice. However, the effectiveness of acupuncture treatment has not been proved in evidence-based practice. Therefore, we design a multicenter randomized controlled trial to evaluate the efficacy and safety of acupuncture treatment for IGT in people with overweight/obesity. Methods The trial will be conducted at hospitals in three different sites in China. A total of 196 participants will be recruited and randomly assigned at a ratio of 1:1 to either to the acupuncture group or the sham acupuncture (SA) group. Both groups will receive 30 sessions of treatment for 12 consecutive weeks and will be provided with lifestyle intervention and a 24-week follow-up. The primary outcome will be change in the baseline value of 2-h blood glucose (2hPG) on the 12th week. Additionally, the expectancy of acupuncture, blinding, and safety will also be assessed. All statistical analyses will be performed by two-sided test, and a p-value of less than 0.05 will be considered statically significant. Discussion This study aims to provide quantitative clinical evidence of acupuncture effectiveness and safety in treating IGT in people who are overweight/obese. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT05347030].